Posttraumatic growth in breast cancer survivors: does age matter?. Issue 6 (18th February 2016) - Boyle, Chloe C.; Stanton, Annette L.; Ganz, Patricia A.; Bower, Julienne E.
Abstract: Objective: Many women report positive life changes, or posttraumatic growth (PTG), as a result of their experience with breast cancer. However, despite compelling evidence that younger age at diagnosis is associated consistently with greater distress, age has not been integrated into models of PTG. Drawing from the theoretical and empirical literature, we tested whether key correlates (i.e., cancer‐related impact and engagement, positive mood) of PTG varied by age at breast cancer diagnosis. Methods: Participants were 175 women with early stage breast cancer followed from completion of primary treatment through one year post‐treatment. Analyses involved data collected at the one‐year assessment. Results: As hypothesized, correlates of PTG varied significantly as a function of age. Perceived negative impact of the cancer experience was associated with growth for older women ( p = .046), whereas approach‐oriented coping ( p = .004), an expansive time perspective ( p = .007), and positive mood were associated with growth for younger women ( p = .007). Conclusions: PTG may involve distinct processes for women diagnosed at different ages. Consideration of lifespan developmental processes is necessary when studying positive adjustment to cancer. Copyright © 2016 John Wiley & Sons, Ltd.